On the Error Estimates for the Rotational Pressure-Correction Projection Spectral Methods for the Unsteady Stokes Equations (Journal of Computational Mathematics, 2005)
This paper provides an analysis of the rotational form of the pressure-correction methods by spectral approximations for the unsteady Stokes equations. Error estimates in finite time for the fully discrete case are given. Numerical experiences using both spectral and spectral element methods are carried out to confirm the theoretical results.